Analisis Faktor-Faktor Penyebab Rendahnya Minat Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Kristen Di Kelas X SMK Negeri 1 Sigumpar Pada Tahun Ajaran 2023/2024 - Christina Ginting; Rusmauli Simbolon; Senida Harefa; Masniar Sitorus (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The purpose of this study was to determine students' interest in learning in Christian Religious Education subjects in class X SMK Negeri 1 Sigumpar in the 2022/2023 academic year. The method used in this research is quantitative research method with inferential statistical approach. The population is all class X students of SMK Negeri 1 Sigumpar in the 2023/2024 academic year totaling 109 people and a sample of 40 people was determined, namely class X TBSM using Purposive Sampling technique. Data were collected with a positive closed questionnaire of 30 items. The results of data analysis show that student interest in learning Christian Religious Education subjects in class X SMK Negeri 1 Sigumpar in the 2022/2023 academic year is 64.06% and with an average of 2.56 < 2.60 is in the unfavorable category. This data is corroborated by conducting a t test (significance) where the tcount < ttable (α = 0.05; dk = n-2 = 38) is -0.045 < 1.684. Thus Ha is rejected and H0: Analysis of Factors Causing Low Student Learning Interest in Christian Religious Education Subjects in Class X SMK Negeri 1 Sigumpar in the 2023/2024 Academic Year < 2.60 of the expected is accepted.